Dietary repletion with ω3 fatty acid or with COX inhibition reverses cognitive effects in F3 ω3 fatty-acid–deficient mice - Ahmad, Hafandi; Begg, Denovan Patrick; Premaratna, Shirmila D.; Sinclair, Andrew J.; Jois, Mark; Weisinger, Richard S. (American Association for Laboratory Animal Science, 2014)
Dietary deficiency of ω3 fatty acid during development leads to impaired cognitive function. However, the effects of multiple generations of ω3 fatty-acid deficiency on cognitive impairment remain unclear. In addition, we sought to test the hypothesis that the cognitive impairments of ω3 fatty-acid–deficient mice are mediated through the arachidonic acid–cyclooxygenase (COX) pathway. To address these issues, C57BL/6J mice were bred for 3 generations and fed diets either deficient (DEF) or sufficient (SUF) in ω3 fatty acids. At postnatal day 21, the F3 offspring remained on the dam's diet or were switched to the opposite diet, creating 4 groups. In addition, 2 groups that remained on the dam's diet were treated with a COX inhibitor. At 19 wk of age, spatial-recognition memory was tested on a Y-maze. Results showed that 16 wk of SUF diet reversed the cognitive impairment of F3 DEF mice. However, 16 wk of ω3 fatty-acid–deficient diet impaired the cognitive performance of the F3 SUF mice, which did not differ from that of the F3 DEF mice. These findings suggest that the cognitive deficits after multigenerational maintenance on ω3 fatty-acid–deficient diet are not any greater than are those after deficiency during a single generation. In addition, treatment with a COX inhibitor prevented spatial-recognition deficits in F3 DEF mice. Therefore, cognitive impairment due to dietary ω3 fatty-acid deficiency appears to be mediated by the arachidonic acid–COX pathway and can be prevented by 16 wk of dietary repletion with ω3 fatty acids or COX inhibition.